Discursive Strategies of Indirect Apology in English-Language Personal Communication - E. Yu. Ilyinova; O. S. Volkova; V. A. Litvinova (Дискурс, 2021)
Introduction. The urgency of the paper is due to the increased interest of linguists in the harmony of interaction and polite interpersonal communication maintenance and restoration. By means of discursive parameters of the communicative situation of apology modelling the research aims to identify the linguistic and strategic peculiarities of their realization in the form of direct and indirect apologies, and to describe the discursive and pragmatic specificity of indirect apology scenario, which prevails in the English-language interaction.Methodology and sources. The research is carried out on the material of modern British writers’ original texts (R. Joyce, J. Rowling, R. Golman) and scripts of feature films in English (Bridget Jones’ Diary, directed by Sharon Maguire, Emma – Directed by Douglas McGrath, etc.) selected by means of a continuous selection method, 172 text excerpts verbalize direct or indirect apologies. The speech act of apology, being a unit of the analysis, is aimed at demonstrating awareness of interpersonal relations and polite communication conventions violation. Linguistic-and-pragmatic analysis of direct and indirect apologies application stipulated the use of parametric modelling method, which involves building a model of communicative situation with the identification of constants, or parameters that vary and adapt to the circumstances of their use. The study of the strategic and tactical peculiarities of communicative behavior in situations with explication of indirect apology was performed by using content analysis method. It was accompanied by application of interpretive analysis of motives, reasons and conditions. In the course of the study, content analysis was applied to state out the subject matter of apologizing and forgiveness statements within the framework of a categorical communicative situation and the subsequent description of their lexical, grammatical, and syntactic peculiarities.Results and discussion. In order to restore harmony broken by accidental or deliberate violation of norms and conventions the communicants use direct or indirect apologies in situations of interpersonal interaction. The parametric modelling method application has enabled the identification of scenario realization variability and proved its conformity with direct and indirect apology strategies. The scenario realization mostly depends on the assessment of severity of the damage caused. The pragmatic-and-linguistic peculiarities of direct and indirect apology scenarios development in English speech practice have been considered and described. The immediate apology intention, which is verbalized in t he speech act of forgiveness request, constitutes the basis for direct apology scenario and is intensified by algorithmized sequence of speech-behavioral actions, such as admitting the guilt, giving excuses, shifting blame, communicating feelings, calling for empathy. In situations of indirect apology, as compared with the direct apology scenario, the replacement of a request for forgiveness by means of one or several speech actions is observed, which confirms the hypothesis of their compensating function in English-speaking interpersonal communication. The paper presents the results of a quantitative and qualitative calculation, which has enabled the researchers to draw a conclusion about the strategic preferences of English-speaking communicants, their gender-stipulated choice, frequency and effectiveness of speech actions application whilst the identified variants of apology scenarios implementation.Conclusion. The discursive strategies of indirect apology, which are expressed by means of speech acts of fault intensification and minimizing, uttered in case of offence or damage of various degree caused to a person, are viewed as value -oriented means of interpersonal relations regulation in the English-speaking community. They reveal the specificity of communicative self-distancing and personal space preservation.